A razoável duração do processo e agarantia constitucional de uma tutela jurisdicional eftiva: atuação ex officio do magistrado na concessão da antecipação da tutela - Loureiro, Mayrenne Trigueiro Pereira (2010)
This dissertation is situated in the area of procedural law and aims to identify the existence of the principle of reasonable lasting of the process its historical evolution and the consequences of its inclusion in the Federal Constitution of 1988 in the 5th article, LXXIII. The main objective is to delimitate the concept and its influence in judicial decision that are preoccupied with procedural effectiveness and for that the elements of European Court of Human Rights will be analyzed. This study is held under the dialetic-hermeneutic method with focus on Procedural Law whose basis is set in Constitution. The main issue is centered historically and developed in the scenario of the Amendment number 45/04 witch suffered a great influence from the Document 319 of the World Bank. The basis, ways to conceive and the conditions to the urgency tutelage are studied with focus on the advances in order to avoid the damages caused by the excessive delay in solving the judicial cases. The article 273 in the Brazilian Civil Procedural Code, witch regulates the urgency tutelage, urges for a wider look of its content, imposing an obligation for the judge and not a mere faculty. The most important conclusion is to make possible the effectiveness of the process with proper, useful and fair decisions so that the access to Justice does not function as a more formality